Solutions for the weighting problem of regional aid indicators when changing to one model for Germany - Schwengler, Barbara; Binder, Jan (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
All German regions are examined in regular intervals to select eligible regions. The delimitation of assisted areas is based on a general indicator model that contains indicators of the regional income and labour market situation. Up to now the need for assistance in the regions in West and East Germany has been examined with separate models. When changing to a model for all German regions, that combines different indicators, there are several not explainable effects in the ranking of the regions. This article tries to explain these differences in ranking and offers solutions for this problem.